Surface modification of aerosol-assisted CVD produced TiO2 thin film for dye sensitised solar cell - Lim, Su Pei; Huang, Nay Ming; Lim, Hong Ngee; Mazhar, Muhammad (Hindawi Publishing Corporation, 2014)
We report a simple and convenient method for the preparation of Ag/TiO2 thin films supported on indium tin oxide, which was achieved by sonochemical deposition of Ag+ on aerosol-assisted chemical vapour deposited TiO2 thin films. Posttreatment was performed on the film by immersion in HCl. The as-prepared composite film was characterised by X-ray diffraction, ultraviolet-visible absorption spectroscopy, Raman spectroscopy, and field emission scanning electron microscopy. The photoelectrochemical measurements and characterisation showed approximately fivefold increase in photocurrent density generation and approximately sevenfold enhancement in dye sensitiser solar cell (DSSC) conversion efficiency, which was achieved after modification of the TiO2 film with HCl posttreatment and Ag particle deposition. The improved photocurrent density of 933.30 A/cm2, as well as DSSC power conversion efficiency of 3.63% with high stability, is an indication that the as-synthesised thin film is a potential candidate for solar energy conversion applications.